Customer valuation model: applied to a foodservice commodities supplier - Alexandre, Victor Manuel Mónica Monteiro (2013)
In last few years, terms like customer centric organization; customer focused strategies; customer metrics and customer value assessment have became buzzwords in the organizations. Independently from which angle managers are grasping these concepts, a common denominator seems to accede that customers are probably the most valuable assets in a company. However, most of costumer value assessments are confined to sales revenues analysis. In this document, several customer value models are assessed, in order to evaluate which can be used as a metric and as a managerial tool, able be applied to market particularities of a foodservice food products supplier. The author selected CLV model as the base model to assess customer values, adapting it to the presented case study. In addition to this model, it was developed a complementary scoring model to balance qualitatively the adapted CLV outputs. The two models working together are the proposed solution to assess the case study customers’ value.